Inovação em serviços para a base da pirâmide - Oliveira, Gibson Meira (2015)
The bottom of the social pyramid in Brazil concentrates many people. Innovating the services offered to them means including consumers that were neglected or would otherwise remain poorly assisted by the existing offers, thus potentializing business opportunities to firms that are seeking a new market. In this context, this research aimed to analyze how companies are dealing with service innovation to cater to consumers at the bottom of the pyramid. More specifically, it aimed to identify the innovations adopted by firms, classify the types of innovation and propose a framework to better explain them. Methodology included multiple case studies; three firms that offer services to such public. Data were collected by means of semi-structured interviews, direct observations and documents. Data for each case was both individually analyzed and cross-examined. Results showed that in order to serve the bottom of the pyramid firms have developed market and process innovations, and also implemented – throughout their trajectories – improvement innovation, incremental innovation and formalization innovation. Through the transilience map it was possible to notice that two out of the three firms studied developed new competencies to match the needs of the bottom of the pyramid. In addition, it is understood that there may be an alignment between the transilience map and the disruptive innovation concepts. The three firms showed partial or total adherence to the proposed framework; in some cases, there was a need to change the type of service offered. It was concluded that although disruptive innovations are aimed at a low income consumers it takes more than just those to serve this public. Furthermore, in the cases analyzed, the service sector possesses an innovation dynamics that is contrary to the technical approach, since technology is not the major driver for innovation. However, this element becomes a support that allows for constant improvement in the service offered.